On‐Demand Control of the Photochromic Properties of Naphthopyrans. Issue 2 (31st October 2018) - Kuroiwa, Hayato; Inagaki, Yuki; Mutoh, Katsuya; Abe, Jiro
Abstract: Photofunctional compounds have emerged as critically important materials for both fundamental studies and industrial applications. Control of the thermal decoloration speed to within several seconds while sustaining satisfactory photochromic colorability is an important challenge for the application of such materials to photochromic lenses and smart windows. Photochromic naphthopyran derivatives are utilized for photochromic lenses because of their high durability and easily controllable colorability. However, the residual color imparted by the long‐lived transient species upon ceasing light irradiation remains a hindrance to practical applications. In this study, a strategy is demonstrated for on‐demand control of the thermal decoloration speed of the transient colored species of naphthopyran derivatives. The increase in the ring‐size of the alkylenedioxy moiety on the naphthopyrans accelerates the thermal back‐reaction independently of the maximum‐absorption wavelength of the colored isomer, leading to the realization of yellow‐, red‐, and blue‐photochromic naphthopyrans with similar thermal fading speeds. This novel molecular design provides a strategy for the future development of advanced photoresponsive materials. Abstract : The control of thermal decoloration speed to within several seconds while sustaining satisfactory photochromic colorability is an important challenge for the development of advanced photochromic materials. The thermal back‐reaction speeds of naphthopyrans having an alkylenedioxy moiety can be easily controlled independently of the absorption maxima of the colored species by changing the alkylene chain length of the alkylenedioxy moiety.